The effects of growth hormone on the outcomes of in vitro fertilization and embryo transfer in age-grouped patients with decreased ovarian reserve: a prospective cohort study - Chen, Jiexiu; Kong, Xumei; Luan, Zonghui; Qiu, Yu; Chen, Shiqi; Li−Ling, Jesse; Gong, Yan (Frontiers in Endocrinology, 2025)
BackgroundGrowth hormone (GH) could improve the outcomes of in vitro fertilization and embryo transfer (IVF-ET) in patients with decreased ovarian reserve (DOR), but which age group will benefit the most has remained controversial. This study aims to explore the outcome of IVF-ET among differently aged patients with DOR treated with GH.MethodsA total of 846 patients with DOR undergoing IVF-ET from May 2018 to June 2023 at the Reproductive Medicine Center of Sichuan Provincial Women’s and Children’s Hospital were prospectively enrolled. The patients were divided into group A (< 35 year old, n = 399), group B (35 ~ 40 year old, n = 286), and group C (> 40 year old, n = 161). Each group was sub-divided into the GH part and the control part, with the former receiving pretreatment with GH 4 IU/day on day 2 of the previous menstrual cycle before the injection of gonadotrophin (Gn) until the trigger day. The ovarian stimulation protocol was gonadotrophin-releasing hormone antagonist (GnRH-A) or long-acting GnRH agonist protocol. The quality of oocytes and embryos and the outcome of pregnancy were compared.ResultsIn group B, the number (1.16 ± 0.12 vs. 0.74 ± 0.09) and rate (34.27% vs. 23.90%) of high-quality cleavage embryos, rate of implantation (32.37% vs. 22.35%), clinical pregnancy (48.98% vs. 33.67%), and live birth (44.90% vs. 29.59%) were significantly higher, whereas the canceled oocyte retrieval rate was significantly lower (1.49% vs. 6.58%) in the GH part than those of the control part (P < 0.05). In group B, the duration and dose of Gn, number of oocyte retrieved, and rates of normal fertilization, cleavage embryo, blastocyst, high-quality blastocyst, and early miscarriage were not significantly different between the GH and control parts (P > 0.05). In groups A and C, no significant difference was detected in the quality of embryos and outcomes of embryo transfer with or without pretreatment (P > 0.05).ConclusionGH could improve the quality of embryos and live birth rate for patients with DOR aged 35–40 years old.